Carbon for soils, not soils for carbon. Issue 9 (16th January 2023) - Moinet, Gabriel Y. K.; Hijbeek, Renske; van Vuuren, Detlef P.; Giller, Ken E.
Abstract: The role of soil organic carbon (SOC) sequestration as a 'win‐win' solution to both climate change and food insecurity receives an increasing promotion. The opportunity may be too good to be missed! Yet the tremendous complexity of the two issues at stake calls for a detailed and nuanced examination of any potential solution, no matter how appealing. Here, we critically re‐examine the benefits of global SOC sequestration strategies on both climate change mitigation and food production. While estimated contributions of SOC sequestration to climate change vary, almost none take SOC saturation into account. Here, we show that including saturation in estimations decreases any potential contribution of SOC sequestration to climate change mitigation by 53%–81% towards 2100. In addition, reviewing more than 21 meta‐analyses, we found that observed yield effects of increasing SOC are inconsistent, ranging from negative to neutral to positive. We find that the promise of a win‐win outcome is confirmed only when specific land management practices are applied under specific conditions. Therefore, we argue that the existing knowledge base does not justify the current trend to set global agendas focusing first and foremost on SOC sequestration. Away from climate‐smart soils, we need a shift towards soil‐smart agriculture, adaptative and adapted to each local context, and where multiple soil functions are quantified concurrently. Only such comprehensive assessments will allow synergies for land sustainability to be maximised and agronomic requirements for food security to be fulfilled. This implies moving away from global targets for SOC in agricultural soils. SOC sequestration may occur along this pathway and contribute to climate change mitigation and should be regarded as a co‐benefit. Abstract : Conceptual figure illustrating potential conflicts between soil organic carbon (SOC) sequestration and food production. The figure depicts two hypothetical cases in which crop residues are removed from one field after harvest to be applied as OM inputs to another crop field. In panel a, residues are transferred from a sandy soil to a clay soil. After some years, a new equilibrium for SOC stock is reached. The clay soil gains more SOC than the sandy soil loses, due to its higher C stabilisation capacity (Kirschbaum et al.,  2020). Therefore the net overall effect is that C is sequestered, to the benefit of climate (provided that no additional N2 O or CH4 emissions would arise). The clay soil also sees crop yield increasing, but not as much as the yield in the sandy soil decreases, due to the stronger yield effect of organic amendments in sandy than clay soils (Hijbeek et al.,  2017; Zomer et al.,  2017). The net effect for yield is that less crops are produced overall. The reciprocal transfer, in panel b, leads to mirrored effects: Small yield loss in the clay soil and high yield gain in the sandy soil, and large CO2 emissions in clay soil and small SOC sequestration in the sandy soil with an overall SOC loss and aggravated climate change, but more food produced overall. Importantly, assuming that each field is owned by a different farmer, someone always loses. This clearly illustrates that local win‐win scenarios can occur at the expense of fertility elsewhere.